Peran Perempuan dalam Ekonomi Kreatif: Tantangan dan Peluang di Tengah Masalah Finansial Keluarga Studi Kasus: Nagari Sungai Tunu Barat, Pesisir Selatan, 2024-2025 - Handayani, Revi; Mayeni, Riska; Wiwita, Risma; Pratama, Bhaik; Maidani, Vivin; Ningsih, Wahyu (Jurnal Gema Ngabdi, 2025)
This community service program is motivated by the low economic value added and limited marketing of products among groups of women fish vendors in Kanagarian Sungai Tunu Barat, Ranah Pesisir District, Pesisir Selatan Regency. The program aims to improve the partners’ knowledge and skills in processing marine products into frozen food, implementing digital marketing, and conducting simple financial record-keeping as an effort to strengthen creative economy activities based on micro, small, and medium enterprises (MSMEs). The program was implemented under the Pengabdian Masyarakat Pemula (PMP) grant scheme of Kemendiktisaintek 2025 over the period of July–December 2025 with three site visits, using methods of socialization, training, mentoring, discussion, as well as monitoring and evaluation. Data were collected through observation, interviews, pre–post questionnaires, practical assessment sheets, and documentation, and were analyzed descriptively using qualitative and simple quantitative approaches. The results show an increase in participants’ knowledge regarding marine product processing and digital marketing; more than 70% of participants were able to produce fish and shrimp meatballs and nuggets according to the procedures, and approximately 80% of participants began to utilize social media to promote their products. The implementation of financial record-keeping enabled partners to start separating capital from profit, while those who actively produced and marketed processed products experienced an increase in daily income of around 30–40%. It is concluded that this integrated mentoring model is effective in enhancing the capacity of women fish vendors and has the potential to be replicated in other coastal communities with appropriate local contextualization.